Factibilidad para la implementación de un establecimiento de juego de bolos (bowling) en la parroquia de Vilcabamba, cantón Loja, Provincia de Loja - Jumbo Capa, Ronie Francisco (2017)
The parish of Vilcabamba is currently run by a market of entertainment services and known by its inhabitants, because so far does not have a Cake Game project, which allow people to have fun in a healthy way, in the market of Training, Are immersed nightclubs bars, soccer courts, basketball, etc. Recreational centers, services that are not used consistently can carry social risks. To solve this problem, the present project poses the following objectives: To carry out a market study to determine the demand and the offer of service in the Parish of Vilcabamba, canton Loja, Loja province. Run a technical study to determine the size of the plant, engineering the project, an end to provide a service in accordance with the requirements of the new company. Perform the legal and administrative study to determine the structure of the company. Carry out an economic study, to establish the total investment of the project, production costs, sales prices and projected budgets. And finally carry out the financial economic evaluation to determine the feasibility of the project, by calculating financial indicators such as current value, internal rate of return, cost benefit ratio, capital recovery period. For the fulfillment of the objectives, a methodology was followed, which allowed the delineation of the steps or processes to be followed, during 8 the investigation, the methodology refers to the methods and techniques that are used the stories such as: the method Analytical, deductive and inductive, with which it was determined in a general and specific manner as well as an analysis to analyze the elements of the positive factors (strengths and opportunities); As well as the negative elements (weaknesses and threats); This will facilitate an accurate diagnosis of the reality of the thesis project and propose the most viable solution alternatives. The survey technique was applied during the market study, on the size of the sample, through which it was possible to gather information regarding the research project. According to the applied methodology, to obtain the sample size, the segmentation of the population has been proceeded, also consisting of the economically active population of both sexes. Being the total of the population of Vilcabamba, of 4,778 inhabitants in the year of 2010 according to the census of the same year. The segment with which the project was worked according to the economically active population is 1,360 people. Once the segment of inhabitants was obtained, a project was carried out until 2021, which resulted in 1,871 inhabitants. The formula was then applied to determine the size of the sample, obtaining a result of 318 surveys. 9 With the applied methodology, the following results were obtained: in terms of demand, the number of potential demands was determined, which is the one who performs some type of sport, whose result according to the surveys is 61%, ie The 1,141 people, 39% correspond to 730 people, as it is known, the population for each year increases according to the growth rate of the INEC by 1.53%, by the potential demand for 2021 last year of the useful life of Project is of 2,347 potential applicants. Of the total number of potential claimants, the number of actual claimants, who are making use of the service, was determined, with a total of 1,073 actual claimants representing 93.78% of the 1,141 potential claimants by 2016, Finalizing in the year 2021 with 1,414 real claimants. Once quantified the number of actual claimants was processed to determine the actual claimants, who are the people who will make use of the new service an offer, the number of actual claimants is 100% of the actual claimants, ie by 2016 The effective Plaintiffs are 1,009 and by 2021 they have 1,328 plaintiffs. With these quantities, the demand projection was continued, taking the economically active population that was determined in the analysis of the applied surveys, whose value for year 1 is 339 to end the year 5 is 380. As for the technical study, it was determined that the installed and used capacities, the capacity used is 4.160 annual services. With this capacity, market share was determined, which is 12% for the year and 10% for year five 10 Once the technical study was completed, the financial study was carried out, detailing the costs of acquiring: fixed assets, deferred assets and covering operating costs, where costs are incurred to generate the service, as well as administrative expenses And sales. Once these items were determined on a monthly basis for the investment and annually for the pro forma budget, the unit cost of the service was continued to be set for year one of $14,35 followed by year two with a monetary value of $ 14,57 And culminates with year five, where the service cost of $ 15,29. With the pro forma budget, I continued to determine the cash flows, a financial indicator used to develop the financial assessment, where the following results were obtained: Net Present Value $ 109,190.77; Internal Rate of Return 48,57%; Relationship Benefit Cost 0.95 ctvs. Of profitability for every dollar invested; Period of Capital Recovery 5 years 3 months and 3 days; According to the sensitivity analysis the project supports an increase in costs up to 34.10% and a decrease in revenues of up to 18,50%.